Phenolic Profile Investigation and Effect of Phedimus stolonifer (S.G. Gmel.)’t Hart on Urease and Serine Proteases - Günbatan T.; İnal Kılıçarslan E.; Dilmaç E.; Sucu M.; Kartal M.; Gürbüz İ. (My University, 2026)
This study aimed to evaluate the in vitro inhibitory activities of Phedimus stolonifer (S.G. Gmel.)’t Hart against urease, chymotrypsin, and trypsin enzymes. Among the tested samples, the n-butanol sub-extract (PS-BuOH) exhibited the strongest chymotrypsin and trypsin inhibitory activities, with IC50 values of 78.82 and 22.19 μg/mL, respectively. The most potent urease inhibitory effects were observed in the ethanol extract (PS-EtOH) and the ethyl acetate sub-extract (PS-EtOAc), with IC50 values of 44.29 and 35.24 μg/mL, respectively. The phenolic compositions of the sub-extracts were analyzed using liquid chromatography- high resolution mass spectrometry (LC-HRMS). Vanillic acid was detected at 55.155 mg/100 g in the hexane sub-extract (PS-Hex). The dichloromethane sub-extract (PS-CH2Cl2) contained vanillic acid (2865.567 mg/100 g), p-coumaric acid (1157.474 mg/100 g), and rhamnocitrin (171.160 mg/100 g), while the PS-EtOAc included (–)-epicatechin gallate (73.918 mg/100 g), vanillic acid (36.263 mg/100 g), and caffeic acid (14.897 mg/100 g). The PS-BuOH was found to be rich in vanillic acid (7.912 mg/100 g), rhamnocitrin (3.119 mg/100 g), and chrysoeriol (1.495 mg/100 g). The aqueous sub-extract (PS-Rw) predominantly contained p- coumaric acid (39.201 mg/100 g) and vanillic acid (18.041 mg/100 g). Consistent with their high phenolic and flavonoid content, the extracts and sub-extracts demonstrated notable antioxidant activities.
Keywords: Eczacılık; Meslek Bilimleri; Farmakognozi; Sağlık Bilimleri; Pharmacology and Therapeutics; Professional Sciences; Pharmacognosy; Health Sciences; Klinik Tıp (Med); Yaşam Bilimleri (Life); Farmakoloji ve Toksikoloji; Farmakoloji ve Eczacılık; Clinical Medicine (Med); Life Sciences (Life); Pharmacology & Toxicology; Pharmacology & Pharmacy; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences